2020
DOI: 10.14744/hf.2020.0006
|View full text |Cite
|
Sign up to set email alerts
|

The utility of noninvasive scores in non-alcoholic fatty liver disease patients with normal and elevated serum transaminases

Abstract: Background and Aim: Noninvasive scores are developed for the estimation of advanced fibrosis, including parameters in addition to transaminases in non-alcoholic fatty liver disease (NAFLD). In this study, we aimed to investigate the diagnostic performances of Fibrosis-4 (FIB-4) and NAFLD Fibrosis Score (NFS) in the estimation of advanced fibrosis comparing patients with normal and elevated transaminases. Material and Methods: We retrospectively analyzed the prospectively collected data of a total of 407 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 33 publications
1
39
1
Order By: Relevance
“…18 A recent study found that the optimal FIB-4 cut-off value in NASH patients for the identification of advanced fibrosis was >1.3 in the literature. 29 However, for identifying HCC risk, we showed that a cut-off value of 2 would be more appropriate.…”
Section: Discussionmentioning
confidence: 90%
“…18 A recent study found that the optimal FIB-4 cut-off value in NASH patients for the identification of advanced fibrosis was >1.3 in the literature. 29 However, for identifying HCC risk, we showed that a cut-off value of 2 would be more appropriate.…”
Section: Discussionmentioning
confidence: 90%
“…As recommended in the major guidelines, non-invasive fibrosis scores as FIB-4 and NFS are useful diagnostic modalities in estimation of advanced fibrosis [ 2 , 24 ]. They show acceptable diagnostic performance both in patients with elevated and normal transaminase levels [ 52 ]. Using FIB-4 for our sample, we found respectively 89.4%, 10.0% and 0.5% (0.1% missing) respondents with eALT to have low, indeterminate or high risk of advanced fibrosis using < 1.45 and > 3.25 as cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis-4 score (FIB-4; based on patient age, platelet count, AST, and ALT [ 10 ]) and NAFLD fibrosis score (NFS; based on patient age, BMI, platelet count, AST to ALT ratio, albumin, and the presence of diabetes/impaired glucose tolerance [ 11 ]) were calculated. Kaya et al [ 12 ] have previously advised that FIB-4 and NFS scores have an acceptable diagnostic performance in the exclusion of advanced fibrosis in patients with normal or elevated transaminases. FIB-4 scores of < 1.3 and > 2.67 indicate a low and high risk for advanced fibrosis, respectively [ 13 , 14 ]; NFS < –1.455 indicates that advanced fibrosis is unlikely, but a score ≥ 0.67 indicates a high probability of fibrosis [ 11 ].…”
Section: Methodsmentioning
confidence: 99%